2017
DOI: 10.18632/oncotarget.17902
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status is associated with global diabetes prevalence

Abstract: The incidence of diabetes is increasing globally. We investigated the relationship between diabetes prevalence and patient socioeconomic status across multiple countries. We searched PubMed to identify population-based surveys reporting diabetes prevalence between 1990 and May 2016. Search results were filtered, and Human Development Index (HDI) values from the United Nations Development Programme were used to assess socioeconomic status for a given nation. Our analysis included 45 national surveys from 32 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 17 publications
1
26
0
4
Order By: Relevance
“…Although some references do not mention sex as an independent risk factor for T2DM [43], the prevalence of T2DM was reported in several studies to be lower among women [44–46] especially in developed countries [47]. The male excess in the incidence and prevalence of T2DM, which is found in some populations, has been attributed to sex-related differences in insulin sensitivity, consequences of obesity and regional body fat deposition and other contributing factors such as hypertension, smoking and alcohol intake [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Although some references do not mention sex as an independent risk factor for T2DM [43], the prevalence of T2DM was reported in several studies to be lower among women [44–46] especially in developed countries [47]. The male excess in the incidence and prevalence of T2DM, which is found in some populations, has been attributed to sex-related differences in insulin sensitivity, consequences of obesity and regional body fat deposition and other contributing factors such as hypertension, smoking and alcohol intake [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, for the developing countries, there may be some non-negligible differences in change of behavioral lifestyle between lower and higher SES. Taking China for example, during the past four decades of rapid economic growth from a state of poverty and backwardness, the consumption of high energy diets occurs broader and faster in the lower SES than in the higher SES ( 13 ), while higher SES generally increases the adoption of sedentary habits, excessive calorie intake ( 35 ). In other words, some behavioral lifestyle risk of diabetes generally increased both in the lower and higher SES.…”
Section: Discussionmentioning
confidence: 99%
“…Previous social-economic analysis of DED merely focused more on medical expense and economic burden resulted by DED [59,60]. However, according to studies on other chronic disease, it has also been found an increasing trend in the prevalence of chronic diseases in lower income group [61,62]. The plausible explanation for this phenomenon is that individuals in lowerincome countries tended to have less access to health-care services, lower understanding of the disease status, and more unhealthy lifestyle behaviors [63,64].…”
Section: Discussionmentioning
confidence: 99%